Analysis of interphase forces and investigation of their effect on particle transverse motion in particle-laden channel turbulence. (January 2017) - Li, Zhenzhong; Wei, Jinjia; Yu, Bo
Highlights: The relative importance of interphase forces obtained by theoretical analysis agrees well with that calculated by numerical simulation. Integral time scale for Basset force should be no smaller than the particle relaxation time. Basset force and lift force are important relative to the drag force. Particle transverse motion is confirmed to be the main reason for flatter particle velocity profile. Abstract: The current study attempts to investigate the relative importance of interphase forces and their effect on particle transverse motion in a particle-laden channel turbulence using the four-way coupled direct numerical simulation based on the point-particle model. The theoretical methods including the frequency analysis and the dimensional analysis were also derived to estimate the relative importance of interphase forces. Meanwhile, the calculation method of the Basset force was also investigated. It was found that the relative importance of different forces obtained by theoretical method and that obtained by numerical simulation can agree well with each other. The integration time scale should not be shorter than the particle relaxation time and the integration time step can be set as the mean Kolmogorov time scale when calculating the Basset force. The Basset force and lift force were found significant relative to the drag force while the added mass force, the Magnus lift force and the pressure gradient force were negligible. The particle transverse motion was confirmed to be the main reason for flatter particle velocity profile. The effects of different interphase forces on particle transverse motion were investigated in detail. In addition, the combined effects of different forces were also researched.